Research and Field Trial of Uplink Coordinated Multipoint Processing in TD-LTE Network - Qixing Wang; Lifeng He; Yi Zheng; Zhenping Hu; Guangyi Liu; Xing Lin; Lei Li; Butovitsch Peter (Dianxin kexue)
TD-LTE is deployed in the same frequency band to improve spectral usage，which also makes the inter-cell interference（ICI）become one of the main bottlenecks of the network capacity. The test results of the large scale TD-LTE field trial demonstrate more than 70% UE could detect signals from multiple cells. The coordinated multi-point processing（CoMP）technology adopts several cell to jointly transmit/receive signals for UE，which could effectively reduce ICI. Several kinds of uplink CoMP scheme were studied. Especially，the field trial of the uplink CoMP in the realistic TD-LTE network was introduced. The test results show that the ce11-edge UE could achieve 50%～100% throughput gain via the uplink CoMP technology，which significantly improves the user experience.